Pediatric Sarcoma Data Forms a Unique Cluster Measured via the Earth Mover’s Distance - Yongxin Chen (Nature Portfolio, 2017)
Abstract In this note, we combined pediatric sarcoma data from Columbia University with adult sarcoma data collected from TCGA, in order to see if one can automatically discern a unique pediatric cluster in the combined data set. Using a novel clustering pipeline based on optimal transport theory, this turned out to be the case. The overall methodology may find uses for the classification of data from other biological networking problems.